Changes in the Level of Compliance with Construction Workers' Occupational Health and Safety Legal Legislation (2013-2018) in the Five-Year Period - Şahin Tolga Güvel (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2022)
The construction sector is one of the those with the highest number of occupational accidents. There are problems in the implementation of legal regulations on occupational health and safety in the sector. In this study, the questionnaire answered by the construction workers in 2013, was repeated in 2018. Considering the data obtained from studies and legal regulations, the survey results from the questionnaire of in 2013 and 2018 are compared. The results of the comparison indicate the change in the five-year period between 2013 and 2018. The results are examined for the level of compliance of the construction workers with the legal regulations on occupational health and safety. According to this study, some improvements has been achieved in this five-year period at occupational health and safety legislation in construction sector in Turkey.